A critical approach to the development of blended medical communication training materials - Van de Poel, Kris; Fourie, Christine (Stellenbosch Papers in Linguistics Plus, 2014)
Effective communication between doctors and patients improves patient health outcomes (Hewett et al. 2009; Stewart 1995; Watson et al. 2012), and communication skills courses have become an integrated component of the medical curriculum. However, language-discordant contexts are not fully provided for yet, since “[l]anguage support guides (such as the Calgary-Cambridge guides; Silverman et al. 2005) generally target native speakers rather than language learners, and typically mention the use of a second or foreign language as just one of many issues in cross-cultural communication without providing any solutions or prescriptions to address ensuing communication problems” (Gasiorek and Van de Poel 2012:372). In a South African professional healthcare context, communication challenges are manifold because of the number of languages and cultures involved and because of the diverse views on the nature of a medical encounter. South African public healthcare is further hampered by a lack of doctors (KZN Department of Health 2013). Given the need for tailored communication materials, a new vocational training course in Afrikaans as a second language was introduced for first-year medical students at one South African university applying a blended learning approach (i.e. restricted contact teaching and autonomous online learning). To facilitate the development and implementation process, the European project Medics on the Move (MoM) was adapted and adopted as a communication tool. This paper addresses principles and practices underlying the MoM materials as part of the process of adapting the vocational training concept to the specific South African context, needs and learners. The development process is presented as an integral part of a comprehensive needs analysis (Brown 1995), at the end of which new questions and needs are identified. The results corroborate that MoM-SA is a dynamic and effective teaching/learning tool which functions as a language support system that helps build skills for a multilingual professional environment.